Essessment of effectiveness of management by quality of general secondary education at region - Одайник, Світлана Федорівна (ScienceRise: Pedagogical Education, 2016)
The article is defined the problem of assessment of effectiveness of management activity; it is grounded criteria, indicators and levels of management effectiveness by quality of general secondary education; it is analyzed different approaches to evaluate the effectiveness of management activity; the attention is accented on the fact that presence of theoretically worked out system of assessment gave the possibility to assess in objective way the effectiveness by quality of management of general secondary education at the region; it is proved that the specialists of the organs of management of regional education, school leaders, district methodologists of methodological offices were not familiar with the mechanisms of quality management of general secondary education and required implementation of effective means of managerial influence; it is made the analysis of key tendencies and approaches to assess the quality of education as basis for its functioning and development; it is highlighted the levels of efficiency of management by quality at general secondary education at the region: elementary, middle, sufficient, high; it is established that the specificity of management by general secondary education at the region was the interdependence of internal (at the level of general educational institution) and external (at the level of local and regional management) of assessment of quality of education; it is grounded notions and categories that revealed the scientific aspects of management by quality of secondary education at the region